Aspects in monopoly capitalism in South Africa - Innes, Duncan (My University, 1983)
The main argument of this article is that capitalism in South Africa has undergone a fundamental change over the last few decades. Essentially, it would seem that the economy has been transformed over this period from being based on conditions of small-scale competitive capitalism to conditions of large-scale monopoly capitalism. As we shall see, this has involved significant changes in the structure and form of production, in the nature of the firm and in the relationship between companies and the workers.
African Studies Seminar series. Paper presented September, 1983
Keywords: Monopolies. South Africa; Capitalism